Effect of cryotherapy duration on experimentally induced connective tissue inflammation in vivo - Jorge Vera; Mayra Alejandra Castro-Nuñez; María Fernanda Troncoso-Cibrian; Ana Gabriela Carrillo-Varguez; Edgar Ramiro Méndez Sánchez; Viviana Sarmiento; Lourdes Lanzagorta-Rebollo; Prasanna Neelakantan; Monica Romero; Ana Arias (Restorative Dentistry & Endodontics, 2023)
ObjectivesThis study tested the hypothesis that cryotherapy duration influences lipopolysaccharide (LPS)-induced inflammation in a rat model.Materials and MethodsSix Wistar rats (Rattus norvegicus albinus) were used. Five sites were selected per animal and divided into 5 groups: a negative control group (NC), 2 positive control groups (PC1 and PC2), and 2 experimental groups (E1 and E2). Cryotherapy was applied for 1 minute (E1) or 5 minutes (E2). An acute inflammatory response was induced in the PC and E groups via subcutaneous administration of 0.5 mL/kg. In the PC2 group, a catheter was inserted without additional treatment. For the E1 and E2 groups, 2.5°C saline solution was administered through the implanted catheters for 1 and 5 minutes, respectively. The rats were sacrificed, and samples were obtained and processed for histological analysis, specifically examining the presence of polymorphonuclear neutrophils and hemorrhage. The χ2 test was used to compare the presence of acute inflammation across groups. Dependent variables were compared using the linear-by-linear association test.ResultsInflammation and hemorrhage varied significantly among the groups (p = 0.001). A significantly higher degree of acute inflammation was detected (p = 0.0002) in the PC and E1 samples than in the E2 group, in which cryotherapy was administered for 5 minutes. The PC and E1 groups also exhibited significantly greater numbers of neutrophils (p = 0.007), which were essentially absent in both the NC and E2 groups.ConclusionsCryotherapy administration for 5 minutes reduced the acute inflammation associated with LPS and catheter implantation.